2001
DOI: 10.1093/milmed/166.11.1023
|View full text |Cite
|
Sign up to set email alerts
|

Machete Injuries in Haiti

Abstract: Machete-related wounds are a source of appreciable morbidity in many developing nations. We describe a case of radial nerve injury resulting from a machete attack in Haiti. Twenty-two additional cases of machete-related wounds treated during a 3-month humanitarian mission to Haiti are reported. Sixty-five percent were accidental in nature, occurring from a variety of routine activities, whereas the remainder were secondary to assaults. The upper extremity was injured in 85% of the cases, often resulting in com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Of these, 126 were selected for review of the full text after primary screening, and 67 were judged to meet the criteria for inclusion in the present study[78910111213141516171819202122232425262728293031323334353637383940414243444546474849505152535455565758596061626364656667686970717273]. …”
Section: Resultsmentioning
confidence: 99%
“…Of these, 126 were selected for review of the full text after primary screening, and 67 were judged to meet the criteria for inclusion in the present study[78910111213141516171819202122232425262728293031323334353637383940414243444546474849505152535455565758596061626364656667686970717273]. …”
Section: Resultsmentioning
confidence: 99%
“…The early presentation witnessed here may have occurred due to the emergency nature of the cases and pressure from police personnel on the victims to get medical treatment and report. Wiedeman et al [5] reported that over 60% of their cases presented after 24 h of injury.…”
Section: Discussionmentioning
confidence: 99%
“…Our patients were aged between 21 and 30 years with a mean age of 24.8 years, this is similar to findings from other studies. [4,5] This implies that the productive age-group is mainly involved and thus may result in far reaching negative impact on the socio-economic growth of the nation. The two university students that are presented in this report could have been victims of secret cult groups' rivalry, which are common on University campuses.…”
Section: Discussionmentioning
confidence: 99%
“…Machete-related wounds are a leading cause of morbidity in developing nations. [1][2][3][4] Historically, these injuries have been underreported. 2,3 However, they are associated with significant physical, interpersonal, economic, and societal costs.…”
mentioning
confidence: 99%
“…6 Existing literature is mainly comprised of case reports and small-center studies. [1][2][3][4][7][8][9] There is only one study detailing the management of machete injuries at a level-one trauma center in the United States. This study by Donnally et al described the management of machete injuries in 48 patients during an 8-year time period.…”
mentioning
confidence: 99%